2018
DOI: 10.2106/jbjs.cc.17.00204
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Reverse Shoulder Arthroplasty Following a Fracture-Dislocation with a Brachial Plexus Palsy

Abstract: Acute RSA with tuberosity repair may be a reasonable treatment modality in the setting of an acute brachial plexus palsy following a comminuted fracture-dislocation of the proximal aspect of the humerus in an elderly patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 19 publications
(22 reference statements)
0
3
0
Order By: Relevance
“… 4 , 19 Previous case reports of PHFs with similar associated injuries treated with RSA have resulted in relatively good outcomes and influenced the decision on orthopedic fixation in this case. 1 , 5 , 7 This case should provide physicians with another piece of evidence for the utility of RSAs with this specific injury scenario given the patient’s outcome at two years and restoration of functional status. However, physicians should also be cautious of the potential for an extended recovery course with an axillary nerve palsy and should counsel patients accordingly with these injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 , 19 Previous case reports of PHFs with similar associated injuries treated with RSA have resulted in relatively good outcomes and influenced the decision on orthopedic fixation in this case. 1 , 5 , 7 This case should provide physicians with another piece of evidence for the utility of RSAs with this specific injury scenario given the patient’s outcome at two years and restoration of functional status. However, physicians should also be cautious of the potential for an extended recovery course with an axillary nerve palsy and should counsel patients accordingly with these injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Previously, axillary nerve injury had been considered a relative contraindication for RSA due to the theoretical risk of dislocation, but recent literature has argued against this. 3 , 5 Recent systematic reviews have also shown slightly better outcomes for primary RSA for elderly PHF as compared to salvage after trying nonoperative treatment. 9 Based on current evidence and surgeon preference, RSA was chosen as the definitive treatment modality for this patient.…”
mentioning
confidence: 99%
“…71,72 With undetected axillary nerve lesions, the resultant decrease in deltoid tone can lead to a higher risk of instability, and tuberosity repair is particularly crucial to enhance stability. 73 The literature suggests the condition and healing of the tuberosities is significantly associated with postoperative instability when RSA is used to treat PHFs. 74,75 Similarly, loosening of the humeral component can present problems when RSA is used to treat fractures.…”
Section: Complicationsmentioning
confidence: 99%